Bedaquiline for the Treatment of Multidrug-resistant Tuberculosis in the United States - Mase, Sundari; Chorba, Terence; Parks, Samuel; Belanger, Ann; Dworkin, Felicia; Seaworth, Barbara; Warkentin, Jon; Barry, Pennan; Shah, Neha (Clinical infectious diseases, 2020)
In 2012, the Food and Drug Administration approved use of bedaquiline fumarate as part of combination therapy for multidrug-resistant tuberculosis (MDR TB). We describe treatment outcomes, safety, and tolerability of bedaquiline in our case series. Data on patients started on bedaquiline for MDR TB between September 2012 and August 2016 were collected retrospectively through 4 TB programs using a standardized abstraction tool. Data were analyzed using univariate methods. Adverse events were graded using the Common Terminology Criteria for Adverse Events. Of 14 patients, 7 (50%) had MDR, 4 (29%) had pre-extensively drug-resistant (XDR), and 3 (21%) had XDR TB. All had pulmonary TB, 5 (36%) had pulmonary and extrapulmonary TB, and 9/13 (69%) were smear positive. One patient (7%) had HIV coinfection, 5 (36%) had diabetes mellitus, and 5/14 (36%) had previous treatment TB. All patients were non-US-born and 5/14 (36%) had private insurance. All patients achieved sputum culture conversion within a mean of 71 days (26-116); 5 after starting bedaquiline. Twelve (86%) completed treatment and 1 (7%) moved out of the country. One patient (7%) had QTc prolongation >500 milliseconds and died 20 months after discontinuing bedaquiline of a cause not attributable to the drug. Common adverse events were peripheral neuropathy 7/14 (50%), not customarily associated with bedaquiline use, and QTc prolongation 6/14 (43%). Of 14 patients, 1 (7%) had an adverse event necessitating bedaquiline discontinuation. Safety, culture conversion, and treatment completion in this series (7%) support use of bedaquiline for the treatment of MDR/XDR TB.